MOTOR VEHICLE TEST QUEUE SYSTEM (Case Study in the Implementation Unit for Periodic Testing of Motorized Vehicles at the Gowa Regency Transportation Service) - Anggraeni Damayanti Regards (Scientium Management Review, 2023)
This study aims to find out how the service system is implemented in the Motorized Vehicle Periodic Test Executor Unit of the Gowa Regency Transportation Service to test the speed of service and provide suggestions so that service accuracy occurs and service effectiveness is created. This study uses a quantitative approach, the data used is primary data, a sample of 100 samples with data analysis method using the formula Average hourly customer arrival rate (λ) Average hourly service level (μ) Number of service facilities (c) Level usability of the service system (P) Average number of customers in the system (L) Average number of customers in the queue (Lq) Average customer time in the system (W) Average time customers are in the queue (Wq ) and qualitative research with a total of 25 informants. And the results of the study show that the average number of customers, the average customer arrival rate per hour (λ) is 10.66 customers per hour, the average customer served per hour (π) is 3.80 customers per hour, the average - the average the number of customers in the system (L) is 2.34 cars per hour, the average number of customers in the queue (Lq) is 1.64 cars per hour. The average time the customer is in the system (Ws) is 13.2 minutes. The average time the customer is in the queue (Wq) is 9 minutes. And the system usability level of 70.13% means that the customer's time to get service at the Motor Vehicle Periodic Test Executor Unit for the Gowa Regency Transportation Service has not gone well. The results of research interviews with 25 informants at the Motor Vehicle Periodic Test Executor Unit at the Gowa Regency Transportation Service stated that in the Tangible section the customer was not satisfied, the customer Reability was satisfied, the customer Responsiveness was satisfied, the Customer Assurance was not satisfied and the Customer Empathy was satisfied. So the level of customer satisfaction at the Motor Vehicle Periodic Test Executor Unit for the Gowa Regency Transportation Service has been running effectively but still needs improvement.